THE POLITIC WRITE IN FOUR CENTURIES: since Michiavelli (1961), Shakespeare (1600), Hobbes (1965) until Rousseau (2001) - Oliveira, Adelson (REVISTA AGON - Ἀγών - ISSN: 2965-422X, 2025)
The presentation of Renaissance European politic: theoretical (Florentine Machiavelli: Il Principe) and practical (Stratfordian Shakespeare: Hamlet piece), is visible to the reader in these works. Considering this politic produced by this English playwright in the practical and expository mode, the bias of his literary critics who defend and question such actions of this character King Claudius is framed. There are two philosofies that only addition for this idea here write about this character administration, they are Hobbes (1965) and Rousseau (2001). This production will contribute for other idea about this King in Hamlet (1600) piece produced by William Shakespeare.